2020
DOI: 10.1097/md.0000000000023006
|View full text |Cite
|
Sign up to set email alerts
|

The single nucleotide polymorphisms of interleukin-10 are associated with the risk of leukaemia

Abstract: Interleukin-10(IL-10) is an immunosuppressive cytokine and plays an important role in inflammation and cancers. Numerous studies have explored the association between single nucleotide polymorphisms of IL-10 and leukemia, but their results were conflicting, so we performed this meta-analysis to elucidate the association between 3 common single nucleotide polymorphisms of IL-10 (rs1800896, rs1800871 and rs1800872) and risk of leukemia. We conducted a comprehensive research in Pubmed, Chinese Biomedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In a recent metanalysis by Gao S. et al, a strong association was found between rs1800896 and leukemia in non-Chinese patients, while the result was negative in Chinese patients [49]. In a study conducted by Aref S on a cohort of 50 CLL patients, they found that the variant allele of rs1800896 was significantly associated with advanced stages of CLL (p < 0.001), a short time to first treatment (p = 0.032), shorter progression-free survival (p = 0.044), and a lower response to treatment (p = 0.003) when compared to the wild genotype [23].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent metanalysis by Gao S. et al, a strong association was found between rs1800896 and leukemia in non-Chinese patients, while the result was negative in Chinese patients [49]. In a study conducted by Aref S on a cohort of 50 CLL patients, they found that the variant allele of rs1800896 was significantly associated with advanced stages of CLL (p < 0.001), a short time to first treatment (p = 0.032), shorter progression-free survival (p = 0.044), and a lower response to treatment (p = 0.003) when compared to the wild genotype [23].…”
Section: Discussionmentioning
confidence: 95%
“…Basabaeen A. et al, on a Sudanese population, again found no association between CLL and rs1800896 [14]. As for rs1800872, in a metanalysis by Gao S., the authors found an association with leukemia risk in non-Chinese patients and no significant association in Chinese patients [49]. The cause of these discordances might lie in the different genetic makeup of the different populations.…”
Section: Discussionmentioning
confidence: 95%
“…The level and activity of cytokines is attributed to single-nucleotide polymorphisms (SNPs) within the promoter region or other regulatory sequences of cytokine genes, which in turn impact the peripheral levels of cytokines and thus pathogenesis [ 22 , 23 , 24 ]. Population studies have indicated a strong association of SNPs with primary immune thrombocytopenia among Caucasian adults [ 25 ], the risk of leukemogenesis in a non-Chinese population [ 26 ], the severity of autoimmune hemolytic anemias in an Italian population [ 27 ], and the risk and overall survival of diffuse large B cell lymphoma in an Arab population [ 28 ]. These reports emphasize the importance of cytokine gene SNPs across diverse populations, shedding light on the intricacies of homeostasis and disease development as well as HLA allele polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported in a meta-analysis of 18 case-control studies. 35 It has been reported that the GG genotype poses a decreased risk of leukemia in comparison to the AG+AA genotype. 35 The current study shows that rs1800896 has no significant associations with age at diagnosis, gender, or subtype of ALL (Table 4).…”
mentioning
confidence: 99%
“…35 It has been reported that the GG genotype poses a decreased risk of leukemia in comparison to the AG+AA genotype. 35 The current study shows that rs1800896 has no significant associations with age at diagnosis, gender, or subtype of ALL (Table 4). This finding is consistent with the literature.…”
mentioning
confidence: 99%